Speciation of mercury in different environmental compartments. Design, development and optimization of analytical methods and procedures - Makiese, Julien Lusilao (My University, 2009)
The widespread use of organometallic compounds and their subsequent release into the environment has created a great environmental concern about the toxicity and effects of these pollutants. Mercury pollution is a growing concern worldwide because its can reach high concentrations in various environmental media and thus adversely affect humans, wildlife and ecosystem functioning. Mercury is present in the environment in different molecular forms with specific biogeochemical transformation and ecotoxicity. Inorganic Hg2+ is the main form in water and sediment samples. Concentration levels of organomercury species is very low (usually ng L-1) in aquatic environments but the toxic effect of these compounds can be significant due to their tendency for bioaccumulation and biomagnification in the food chain. The development of a sensitive, reliable, simple, and cost effective procedure for speciation analysis of mercury in different environmental compartments is currently one of the principal research challenges in environmental analytical chemistry. To this end, this study aimed to develop and optimize analytical methods and procedures for the determination of total mercury and the speciation of inorganic and organic forms of mercury. The hyphenation of gas chromatography and inductively coupled plasma mass spectrometry (GC-ICP-MS) was achieved and used successfully. Rapid and efficient sample preparation procedures based on microwave-assisted extraction for solid samples were developed. The optimized analytical methods and procedures were validated by the analysis of environmental certified reference materials (CRM 015-050 sediment for HgTOT and CRM 463 tuna fish for HgTOT and MeHg). The developed methodologies were finally applied to real environmental samples, namely soil, sediment, water, fish and human hair, collected in some South African regions affected by environmental pollution due to reprocessing of old tailings dumps and chlor-alakali facilities. The study included collection of ancillary data (pH, redox potential) which are critically important for mercury monitoring program. Predictive models of mercury speciation in water samples based on thermodynamic solution equilibria were also established.